Quantitative easing and asset bubbles in a stock-flow consistent framework - Cameron Haas; Tai Young-Taft (Levy Economics Institute of Bard College, 2017)
Ever since the Great Recession, central banks have supplemented their traditional policy tool of setting the short-term interest rate with massive buyouts of assets to extend lines of credit and jolt flagging demand. As with many new policies, there have been a range of reactions from economists, with some extolling quantitative easing's expansionary virtues and others fearing it might invariably lead to overvaluation of assets, instigating economic instability and bubble behavior. To investigate these theories, we combine elements of the models in chapters 5, 10, and 11 of Godley and Lavoie's (2007) Monetary Economics with equations for quantitative easing and endogenous bubbles in a new model. By running the model under a variety of parameters, we study the causal links between quantitative easing, asset overvaluation, and macroeconomic performance. Preliminary results suggest that rather than being pro- or countercyclical, quantitative easing acts as a sort of phase shift with respect to time.
Keywords: E12; E44; E58; E16; E21; 330; Quantitative Easing; Stock-flow Consistency; Macroeconomics